18 Prevalence of iron deficiency among extreme preterm neonates based on Reticulocyte-Hemoglobin levels: a single center cross-sectional study. (21st October 2022) - Sriranjan, Jhanahan; Thomas, Karen; Fusch, Gerhard; Kalata, Christine; Goswami, Ipsita
Abstract: Background: Extreme preterm neonates are at risk of developing iron deficiency due to multiple factors including lack of third trimester placental iron accretion and frequent blood sampling. The true prevalence of iron deficiency in this cohort is not known due to lack of valid markers. Compared to Hemoglobin (Hb) derived from the entire red blood cell population (lifespan 120 days), Hb derived for reticulocytes (lifespan 3 days) is a real-time indicator of functional iron available for erythropoiesis during the previous 3-4 days. Reticulocyte-Hemoglobin (Ret-Hb) levels lower than 29pg can indicate iron deficiency in preterm neonates < 32 weeks gestation with 85% sensitivity and 73% specificity. Objectives: This study aims to measure the prevalence and risk factors of iron deficiency at term equivalent age among extreme preterm neonates based on Ret-Hb levels. Design/Methods: A single center retrospective chart review of neonates born at <= 29 weeks gestation between June 2016 to December 2019. All neonates received routine iron supplementation from 2 weeks postnatal age at 3-4mg/kg/day (birth weight <1Kg) or 2-3mg/kg/day (birth weight>1Kg) to a maximum of 15mg elemental iron as ferrous sulfate or iron fortified formula. Hb, Reticulocyte count, Ret-Hb, Immature reticulocyte fraction (IRF) and mean corpuscular volume (MCV) was measured at 4 weeks postnatal age, 36 weeks corrected gestation, and at discharge. Iron deficiency at term equivalent age was defined as Ret-Hb levels <= 29pg. Results: Among 387 eligible neonates, 187 who had hematological parameters available at term equivalent age were included. The study cohort had a mean gestation of 25.7 (1.6) weeks, birth weight of 863 (220) g, mean SNAPPEII score of 29.2 (19), and gestational age at discharge of 42.7 (7.2) weeks. The prevalence of iron deficiency among neonates < 24 weeks, 24-25 + 6 weeks, 26-27 + 6 weeks, and >=28 weeks was 35.7%, 18.4%, 27.7%, and 15.6% respectively. Male infants were more likely to have iron deficiency at term equivalent [Table 1 ]. The neonates with iron deficiency had higher rates of necrotising enterocolitis [14% versus 8%], laparotomy [14% versus 10%] and postnatal steroids [69% versus 57%] compared to neonates without iron deficiency, however not statistically significant. Ret-Hb levels at 4 weeks postnatal age showed a positive correlation with Ret-Hb levels [Slope 0.58, R 2 squared 0.02] and MCV levels [Slope 0.75, R 2 0.11] at discharge [Figure 1] . Contrary to changes in Hb levels and reticulocyte counts, Ret-Hb levels, MCV and IFR progressively decrease from 4 wks postnatal age to discharge. Conclusion: Despite routine standardized iron supplementation, extreme preterm neonates may have iron-limited erythropoiesis indicated by low Ret-Hb levels at term equivalent age. Lower levels of Ret-Hb at 4 weeks postnatal age was associated with low IRF and low MCV at discharge although Hb levels may remain within acceptable range. Future studies would need to elucidate the impact of iron deficiency at corrected term on long-term outcome. Guidelines should consider incorporating Ret-Hb levels in the workup of anemia of prematurity.